Injury severity measures for predicting return-to-work after a traumatic brain injury. (January 2017) - Chien, Ding-Kuo; Hwang, Hei-Fen; Lin, Mau-Roung
Highlights: Of 5 severity measures, the ISS best explained employment after TBI. The most frequently used measure of TBI severity, GCS, least explained employment. Transportation, cognition, and depression also affected employment after TBI. Abstract: This study compared the ability of five injury severity measures, namely the Abbreviated Injury Scale to the Head (AIS-H), Glasgow Coma Scale (GCS), Glasgow Outcome Scale (GOS), Extended Glasgow Outcome Scale (GOSE), and Injury Severity Score (ISS), to predict return-to-work after a traumatic brain injury (TBI). Furthermore, factors potentially associated with return-to-work were investigated. In total, 207 individuals aged ≤65 years newly diagnosed with a TBI and employed at the time of injury were recruited and followed-up for 1 year by telephone every 3 months. A bivariate proportional hazards model analysis revealed that all five injury severity measures were significantly associated with return-to-work after a TBI. The AIS-H and non-head ISS explained 23.8% of the variation in the duration of returning to work from discharge after hospitalization for a TBI; similarly, the GCS, GOS, GOSE, and ISS respectively accounted for 4.7%, 21.4%, 12.9%, and 48.4% of the variation. A multivariable analysis revealed that individuals with higher injury severity as measured by the ISS (hazard ratio [HR], 0.94; 95% confidence interval [CI], 0.92–0.97), a lack of autonomy in transportation (HR, 2.55; 95% CI, 1.23–5.32), cognitive impairment (HR, 0.47; 95% CI, 0.28–0.79), and depression (HR, 0.97; 95% CI, 0.95–0.99) were significantly less likely to be employed after a TBI. In conclusion, of the five injury severity measures, the ISS may be the most capable measure of predicting return-to-work after a TBI. In addition to injury severity, autonomy in transportation, cognitive function, and the depressive status may also influence the employment status during the first year after a TBI.